An Interface Between Mental Health Systems and the Community: Italian Social Cooperatives. Issue 1 (2nd April 2016) - Laratta, Rosario
ABSTRACT: For more than two decades, Italian B-type social cooperatives have represented a sustainable social business model of working with disadvantaged people, especially the mentally disabled. The purpose of this article is to identify the major factors that make this business model successful. By drawing on his recent work of Italian social cooperatives, including a case study, the author explores organizational goals and repertoires as well as support structures and networks of those organizations. This study explores three major factors that account for the sustainability and growth of this model: good regulation; a supportive system of infrastructures; and democratic operational governance. These make the social cooperative an inspiring example of the outcomes that are possible when the mentally disabled are properly trained in a supportive environment. The social cooperative is a model that could well prove similarly successful if copied in other parts of the world.